PENGARUH LIKUIDITAS, LEVERAGE, STRUKTUR KEPEMILIKAN DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK - Lyandra Aisyah Margie; Habibah Habibah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to obtain empirical evidence regarding the effect of Liquidity, Leverage, Ownership Structure and Profitability on Tax Aggressiveness in pharmaceutical companies listed on the Indonesia Stock Exchange (BEI) 2013-2018. This type of research is associative quantitative and the method of analysis used in this study is multiple linear regression analysis. By using the purposive sampling method, the research sample obtained was 5 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (BEI) with six years of observations from 2013 to 2018. The results showed that simultaneously liquidity, leverage, ownership structure and profitability had a significant effect on tax aggressiveness. However, partially liquidity, leverage, ownership structure and profitability do not have a significant effect on tax aggressiveness